2022
DOI: 10.1002/ddr.21994
|View full text |Cite
|
Sign up to set email alerts
|

α‐Pinene inhibits the growth of cervical cancer cells through its proapoptotic activity by regulating the miR‐34a‐5p/Bcl‐2 signaling axis

Abstract: Purpose α-pinene was a chemical compound which was extracted from pine needles oil, and it exerted effects on various diseases. However, the effect of α-pinene on cervical cancer had not been reported. The goal of this study was to explore the anti-tumor role of α-pinene.Methods Methyl thiazolyl tetrazolium (MTT) method was used to detect cytotoxicity of α-pinene. Flow cytometry was used to quantify the cell cycle and apoptosis. TUNEL staining was also performed for the revalidation of apoptosis. QRT-PCR and w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…At the individual additive level, pathway enrichment results often reflect literature findings. For example, the unclassified additive alpha-pinene (80-56-8) exerts an antitumor effect by inducing G2/M cell cycle arrest. Consistent with this, alpha-pinene’s enriched pathways included G2/M Transition, G2/M DNA Damage Checkpoint, and three other G2/M pathways. Similarly, the Group 1 carcinogen trichloroethylene (79-01-6) enriched Prostate Cancer, Hepatocellular Carcinoma, and four similar pathways, which is consistent with epidemiological studies that linked this chemical to liver and prostate cancer in humans with significant exposures .…”
Section: Discussionmentioning
confidence: 78%
“…At the individual additive level, pathway enrichment results often reflect literature findings. For example, the unclassified additive alpha-pinene (80-56-8) exerts an antitumor effect by inducing G2/M cell cycle arrest. Consistent with this, alpha-pinene’s enriched pathways included G2/M Transition, G2/M DNA Damage Checkpoint, and three other G2/M pathways. Similarly, the Group 1 carcinogen trichloroethylene (79-01-6) enriched Prostate Cancer, Hepatocellular Carcinoma, and four similar pathways, which is consistent with epidemiological studies that linked this chemical to liver and prostate cancer in humans with significant exposures .…”
Section: Discussionmentioning
confidence: 78%
“…12 α-Pinene, the most abundant component of turpentine, can promote apoptosis, and its derivatives have the potential to be used as lead compounds for the development of hepatocellular carcinoma drugs. 13,14 Pine trees themselves can secrete metabolites (such as α-pinene) to defend against the wilt disease caused by pine wood nematodes. 15,16 In addition, camphene and limonene with higher added values can be derived by the isomerization of α-pinene.…”
Section: Introductionmentioning
confidence: 99%
“…For application of ethephon to pine trees, the secreted turpentine was 71.33–76.56%, in which α-pinene content of 37.70–53.31%, and β-pinene content of 34.3–50.41% . α-Pinene, the most abundant component of turpentine, can promote apoptosis, and its derivatives have the potential to be used as lead compounds for the development of hepatocellular carcinoma drugs. , Pine trees themselves can secrete metabolites (such as α-pinene) to defend against the wilt disease caused by pine wood nematodes. , In addition, camphene and limonene with higher added values can be derived by the isomerization of α-pinene. , (−)-Limonene, a component of turpentine, is widely used in food, pharmaceuticals, cosmetics, etc . It has anti-inflammatory, anti-diabetic, antioxidant, and anti-cancer activities in medicine and has positive effects in the treatment of gastric ulcers and asthma .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies have demonstrated that cannabidiol (CBD) contributes to alleviating intestinal inflammation and reducing thermal pain in animals, resulting in a decrease in the expression of inflammatory markers and inhibiting the production of IL-8 (interleukin-8, a proinflammatory cytokine) [ 20 ]. Other studies have shown that CBD reduces the circulating number of neutrophils and inhibits the release of inflammatory cytokines in mice treated with lipopolysaccharide, highlighting its anti-inflammatory role [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds can contribute to various pharmacological properties of cannabis, including anti-inflammatory and antinociceptive effects [ 19 ]. Several studies have evaluated these effects in inflammation management, highlighting monoterpenes such as β-myrcene, α-pinene (inhibition of IL-6, TNF-α, and nitric oxide production and the suppression of MAPK and NF-κB activities in peritoneal macrophages) [ 20 ], limonene (inhibition of cytokines TNF-α, IL-1β, and IL-10 production), and linalool (regulation of K1, voltage-gated Na1, and Ca21 channels). Moreover, sesquiterpenes such as β-caryophyllene (reduction of the expression and production of proinflammatory cytokines, such as IL-1β, IL-6, IL-8, and TNF-α) [ 21 ] and α-humulene (downregulation of iNOS and COX-2 gene expression through the inhibition of NF-κB and AP-1 (ERK and p38) pathways) [ 19 ] have also demonstrated anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%